INSULIN ASPART CAN LEAD MEIOTIC RESUMPTION IN CATFISH, Clarias Grapienus OOCYTES - Syarifuddin, Nurul Wulandari; Warih, Agung Pramana; Soeprijanto, Agus (Jurnal Kedokteran Hewan, 2013)
This study directly tested the hypothesis that the induction of oocyte maturation on catfish Clariasgrapienusby insulin aspartresulted in a transient decrease of oocyte cyclic AMP (cAMP) level due to the increase ofphosphodiesterase (PDE) activity. Under the influence of insulin the germinal vesicle (GV) of the oocyte migrated towards the animal pole (GVM), reached the micropyle, and then dissolved (GVBD). By using different concentrations of insulin aspart i.e., 0 U/ml, 0.01 U/ml, 0.1 U/ml, 1 U/ml and 10 U/ml, optimum amount required was found to be 1U/ml. The number of oocytes incubated for 24 hours with insulin aspartic treatment that undergo meiotic re-initiation can reach the percentage of meiotic resumption oocytes was 82%. The results suggest that catfish oocytes have responsive to sensitive adenylatecyclase and also an active phosphodiesterase system. Addition of the maturation-inducing steroid, a progesterone, stimulated (P0.01) GVBD of catfish oocytes and its combination with insulin aspart showed an additive effect. This information will be important in hormonal manipulation during induced breeding of Indonesian commercial catfish.